INFORMATION SYSTEM FOR ASSESSING THE PROBABILITY OF A RISK EVENT WHEN MAK-ING BIOMEDICAL DECISIONS - Lutskyi, Maksym; Ivanets, Olga; Shavshina, Vladislava (Science-based technologies, 2022)
Risk assessment is an important task in decision making. Quantitative risk assessments in the implementation of treatment and prevention measures allow not only to effectively use the resources of medical institutions, but also create a basis for reducing errors of the first and second kind in making medical decisions. But the formalization of quantitative risk assessment is complicated by the need to take into account a number of factors that may lead to a risk situation (event). Therefore, an important step before the procedure of developing an information system for quantitative risk assessment is to conduct a cause-and-effect analysis of the impact of factors that may cause an event. Improving the procedure for quantifying the occurrence of an adverse event (risk) through the introduction of information technology is an urgent task in implementing the latest trends in medicine, moving from treatment to procedure for prevention and prevention of risk situations. Prevention of adverse events in the treatment of procedures should use a proactive approach, which allows you to implement the concept of preventing adverse events. All this requires the solution of fundamentally new tasks of organizational, technological and innovative nature, their phased implementation, in line with the objectives of practical health care and global trends in its development and forecasting of risk events. In the given research the analysis of risk factors at introduction and operation of the pacemaker is carried out. An automated information system has been developed to quantify the probability of a dangerous event for each individual clinical case based on the method of expert assessments. The peculiarity of this system is the combination of ranking methods in combination with the method of scoring. With the help of the developed information system, experts can determine the severity of each of the influencing factors, and the doctor, in turn, can apply the program in clinical practice by entering patient data, for example at the first reception, get an automated calculation. . The purpose of using this information system is to carry out a preliminary (primary) risk analysis for the patient in the preoperative period based on an assessment of a number of possible causal factors of this risk. The program is also designed to reduce the impact of the human factor in the calculation and automation of the decision-making process.